"We have to learn to cooperate with each other": a qualitative study to explore integration of traditional healers into the provision of HIV self-testing and tuberculosis screening in Eswatini - Bernadette Schausberger; Nqobile Mmema; Velibanti Dlamini; Lenhle Dube; Aung Aung; Bernhard Kerschberger; Iza Ciglenecki; Debrah Vambe; Esther Mukooza; Alison Wringe (BMC, 2021)
Abstract Background Traditional healing plays an important role in healthcare in Eswatini, and innovative collaborations with traditional healers may enable hard-to-reach men to access HIV and tuberculosis diagnostic services. This study explored attitudes towards integration of traditional healers into the provision of HIV self-testing kits and sputum collection containers. Methods A qualitative study was conducted in 2019-2020 in Shiselweni region, Eswatini. Eight male traditional healers were trained on HIV and tuberculosis care including distribution of HIV self-testing kits and sputum collection containers. Attitudes towards the intervention were elicited through in-depth interviews with the eight traditional healers, ten clients, five healthcare workers and seven focus group discussions with community members. Interviews and group discussions were conducted in SiSwati, audio-recorded, translated and transcribed into English. Data were coded inductively and analysed thematically. Results 81 HIV self-testing kits and 24 sputum collection containers were distributed by the healers to 99 clients, with 14% of participants reporting a reactive HIV self-test result. The distribution of sputum containers did not result in any tuberculosis diagnoses, as samples were refused at health centres. Traditional healers perceived themselves as important healthcare providers, and after training, were willing and able to distribute HIV self-test kits and sputum containers to clients. Many saw themselves as peers who could address barriers to health-seeking among Swazi men that reflected hegemonic masculinities and patriarchal attitudes. Traditional healers were considered to provide services that were private, flexible, efficient and non-judgemental, although some clients and community members expressed concerns over confidentiality breaches. Attitudes among health workers were mixed, with some calling for greater collaboration with traditional healers and others expressing doubts about their potential role in promoting HIV and tuberculosis services. Specifically, many health workers did not accept sputum samples collected outside health facilities. Conclusions Offering HIV self-testing kits and sputum containers through traditional healers led to high HIV yields, but no TB diagnoses. The intervention was appreciated by healers' clients, due to the cultural literacy of traditional healers and practical considerations. Scaling-up this approach could bridge testing gaps if traditional healers are supported, but procedures for receiving sputum samples at health facilities need further strengthening.